Penerapan Teknologi LoRa Dalam Sistem Komunikasi Early Warning System Untuk Mitigasi Bencana Tsunami - Hadi Candra; Lathifah Arief; Dody Ichwana Putra (CHIPSET, 2021)
Lora technology is implemented on prototype to carry out a Tsunami early warning system by sending a trigger code to sound the arduino. the sender uses Dragino LoRa LG01 outdoor while on the other side uses Dragino LoRa node and Arduino Mega. Triggers are input data from Dragino LoRa Gateway in form of string of data which is then converted and sent via LoRa communication. The data that arrives at the node will trigger the program to turn on the siren that has been keep in Arduino Mega. The application of this LoRa is to turn on the sire with a maximum distance. In this research also calculated the capacity of resource at the node that will be sent to the Gateway each time the trigger code is sent. Tests carried out in sub-urban areas with several distance parameters. The maximum distance that can be reached is 500 meters with Receive signal strong indicator (RSSI) -95. While the average time span since the trigger is sent untill the siren is sounded is 0.45 seconds.